Historical destiny and national socialism in Heidegger's "Being and time" - Fritsche, Johannes (University of California Press, 1999)
There has been much debate over the relationship of Heidegger's philosophy - in particular his book Being and Timeto his practical involvement with National Socialism. Yet the question has never been addressed through a comparison of Being and Time with other texts on history and politics written at the time. Johannes Fritsche does this, providing a detailed interpretation of the relevant passages in Being and Timeespecially sections 72-77 on fate, community, and society. He analyzes for comparison two other authors who explicitly regarded themselves as rightists - Adolf Hitler (Mein Kampf) and Max Scheler (Formalism in Ethics and other writings) - and two authors on the left - Georg Lukacs (History and Class Consciousness) and Paul Tillich (The Socialist Decision)." "Fritsche concludes that Being and Time is a brilliant summary of right-wing politics in general, which proposes the destruction of liberal society in order to regenerate an idealized community. -- Provided by publisher